Neurophysiological mechanism of the unloading reflex as a prognostic factor in the early stages of idiopathic adolescent scoliosis - Dobosiewicz, K. (Springer-Verlag, 1997)
This paper presents a new neurophysiological method of evaluating the risk of progression in idiopathic scoliosis in the early stages of the disease, by investigating the unloading reflex in paraspinal muscles. The study included 394 patients with scoliosis and 70 healthy children. Latency of the unloading reflex and repeatability of the rebound and silent period were analysed for each reflex evoked. Prolonged latency and minimal number of cycles are the most important factors in the evaluation of progressive idiopathic scoliosis. The method can be used to detect progressive idiopathic scoliosis in the early stages of the disease. The high sensitivity of the method means it can be used as a basis on which to take an early decision to perform surgery.